Die EU-Russland-Beziehungen: eine Ausweitung innenpolitischer Interessen? - DMITRIEVA, ANNA (Rocznik Integracji Europejskiej, 2012)
In the paper, the author emphasizes a new stage in relations between Russia and the EU in 2008, following the election of D. Medvedev for president. This marked the beginning of intensive talks on the extension of the Partnership and Cooperation Agreement (PCA) and the launch of the EU-Russian Partnership for Modernization. These activities failed, which primarily resulted from how the internal situation developed in Russia. The EU observed that democratization in Russia failed to progress, and the guiding motto of the Putin/Medvedev tandem was to gain and maintain power. The EU was particularly critical of the state parliamentary elections in 2011 and presidential elections in 2012. The EU and Russia have different points of view on the development of bilateral relations. Russia expects the EU to provide technological support and abandon visas, whereas the EU expects Russia to observe Western standards of human rights, freedom of the media and an oligarch-free economy. It will be difficult to align the interests of the EU and Russia outside the energy sector, which is the only sector that may stabilize their overall relationship.